Effect of Whole-Body Vibration on Neuromuscular Activation of Leg Muscles During Dynamic Exercises in Individuals With Stroke. Issue 7 (July 2017) - Liao, Lin-Rong; Pang, Marco Yiu Chung
Abstract : Abstract: Liao, L-R, and Pang, MYC. Effect of whole-body vibration on neuromuscular activation of leg muscles during dynamic exercises in individuals with stroke. J Strength Cond Res 31(7): 1954–1962, 2017—This study examined the leg muscle activity during exposure to different whole-body vibration (WBV) intensities while performing various dynamic exercises in patients with chronic stroke. Thirty patients with chronic stroke performed a series of dynamic exercises under 3 conditions: (a) low-intensity WBV (peak acceleration: 0.96 units of gravity of Earth [ g ]), (b) high-intensity WBV (1.61 g), and (c) no WBV. Neuromuscular activation was recorded with surface electromyography (EMG) on bilateral biceps femoris (BF), vastus lateralis, tibialis anterior (TA), and gastrocnemius (GS) in both legs and was reported as EMGrms (root mean square) normalized to % maximal voluntary contraction. The EMG amplitude of all tested muscles was significantly increased by adding WBV during dynamic exercise ( p ⩽ 0.05). The EMG amplitude of BF, TA, and GS during exposure to high-intensity WBV was significantly greater than low-intensity WBV ( p ⩽ 0.05). The increase in EMG amplitude caused by WBV was exercise dependent in GS and TA ( p ⩽ 0.05). The EMG response to WBV in GS and BF in the affected leg was significantly greater than the corresponding muscles in the unaffected leg ( p ⩽ 0.05). The extent of WBV-induced muscle activity was dependent on the dynamic exercise, WBV intensity, and muscle trained among patients with chronic stroke.